Energy subsidy reform and economic sustainability: Egypt vs. Iran - GHAZY, Noha; GHONEIM, Hebatallah (Turkish Economic Review, 2019)
Abstract. This paper illustrates the relationship between energy reforms and economic sustainable development in Egypt and Iran; through analyzing the relation between energy reform and four main macroeconomic variables, namely: budget deficit, energy consumption, inflation and economic growth. The methodology adopted in this paper is a comparative case study between Egypt and Iran, using qualitative descriptive analysis; focusing on the period from 2010 to 2014, as this period is characterized with active subsidy reform efforts for both countries. The paper concludes that reforming energy subsidies generally tends to relief the strain on the public budget, in case it is not accompanied with simultaneous economic difficulties which can deem the reform efforts obsolete, like in the case of Iran. In addition, the responsiveness of energy consumption of a certain fuel to the increase in its price is heavily reliant on its price elasticity of demand. This is represented in the availability of alternative energy sources. Moreover, the effect of the reforms on inflation is normally instantaneous and short-lived and could be mitigated through government intervention; that was clear in the case of Egypt. However, Iran did not show a similar trend as there was a weak correlation between subsidy reforms and inflation. Finally, there tends to be a very weak relationship between subsidy reforms and GDP growth, implying that the effect of other economic factors outweighs that of subsidy reforms. Keywords. Energy subsidy reform, MENA region, Sustainable development. JEL. E62, H23, Q01.